Duels with Continuous Firing - Lang, John Patrick; Kimeldorf, George (Management Science, 1975)
A game-theoretic model is proposed for the generalization of a discrete-fire silent duel to a silent duel with continuous firing. This zero-sum two-person game is solved in the symmetric case. It is shown that pure optimal strategies exist and hence also solve a noisy duel with continuous firing. A solution for the general nonsymmetric duel is conjectured.